ARCHITECTURAL DESIGN OF THE SCHOOL ACADEMIC SYSTEM (E_MENGAJAR) USING THE OPEN GROUP ARCHITECTURE FRAMEWORK (TOGAF) AT SMPN 1 PAGELARAN PRINGSEWU DISTRICT - Yulian, Hengky; Nugroho, Handoyo Widi (Informatika, Universitas Jenderal Soedirman, 2024)
This research aims to design the architecture of a school academic system called E-Teaching at SMPN 1 Pagelaran, Pringsewu Regency, using the Open Group Architecture Framework (TOGAF) framework. This approach was chosen to ensure that the resulting system has a solid structure, is reliable, and is well integrated with the school's business processes. The research method used includes the main stages of TOGAF, namely Preliminary Phase, Architecture Vision, Business Architecture, Information Systems Architecture, Technology Architecture, and Opportunities and Solutions. The results of this research are in the form of an architectural model that includes main components such as student data management, learning administration, academic evaluation, and integration with the school management information system. The implementation of E-Teaching is expected to increase operational efficiency, simplify administrative processes, and support the overall learning process at SMPN 1 Pagelaran. The findings from this research provide a significant contribution to the development of academic information systems in secondary education environments, and show that the application of TOGAF can provide effective results in system architecture design.